Novel oncogenic PDGFRA mutations in pediatric high-grade gliomas - Paugh, Barbara S; Zhu, Xiaoyan; Qu, Chunxu; Endersby, Raelene; Diaz, Alexander K; Zhang, Junyuan; Bax, Dorine A; Carvalho, Diana; Reis, Rui M; Onar-Thomas, Arzu; Broniscer, Alberto; Wetmore, Cynthia; et al. (Cancer research (Chicago, Ill.), 2013)
The outcome for children with high-grade gliomas (HGG) remains dismal, with a 2-year survival rate of only 10% to 30%. Diffuse intrinsic pontine glioma (DIPG) comprise a subset of HGG that arise in the brainstem almost exclusively in children. Genome-wide analyses of copy number imbalances previously showed that platelet-derived growth factor receptor α (PDGFRA) is the most frequent target of focal amplification in pediatric HGGs, including DIPGs. To determine whether PDGFRA is also targeted by more subtle mutations missed by copy number analysis, we sequenced all PDGFRA coding exons from a cohort of pediatric HGGs. Somatic-activating mutations were identified in 14.4% (13 of 90) of nonbrainstem pediatric HGGs and 4.7% (2 of 43) of DIPGs, including missense mutations and in-frame deletions and insertions not previously described. Forty percent of tumors with mutation showed concurrent amplification, whereas 60% carried heterozygous mutations. Six different mutations impacting different domains all resulted in ligand-independent receptor activation that was blocked by small molecule inhibitors of PDGFR. Expression of mutants in p53-null primary mouse astrocytes conferred a proliferative advantage in vitro and generated HGGs in vivo with complete penetrance when implanted into brain. The gene expression signatures of these murine HGGs reflected the spectrum of human diffuse HGGs. PDGFRA intragenic deletion of exons 8 and 9 were previously shown in adult HGG, but were not detected in 83 nonbrainstem pediatric HGG and 57 DIPGs. Thus, a distinct spectrum of mutations confers constitutive receptor activation and oncogenic activity to PDGFRα in childhood HGG.